Functional Carbon Nanomesh Clusters. (16th June 2017) - Li, Changxia; Li, Zengling; Cheng, Zhihua; Ding, Xiaoteng; Zhang, Jing; Huang, Rudan; Qu, Liangti
Abstract : A new type of atom‐thin carbon nanomesh clusters (CMCs) is prepared through a self‐sacrificial and morphology‐reserved thermal transformation of electrodeposited zinc coordination polymer (Zn‐CP). Such a unique structure can effectively inhibit the sheet stacking due to the self‐formed cluster morphology of Zn‐CP. The clusters are composed of nitrogen‐doped, continuous, interconnected, one‐/two‐atom‐thick carbon nanosheets, which not only effectively inhibit the sheet stacking but also significantly benefit ion transport. As a result, as active electrode material of supercapacitor in aqueous electrolytes, the resultant nitrogen‐doped CMC (N‐CMC) yields a capacitance of up to 984 F g −1 at 0.5 A g −1 and excellent cycling stability with 137% of its initial capacitance after 40 000 cycles, both higher than most of reported graphene‐based and carbon‐based electrode materials. On the other hand, the final N‐doped CMC also exhibits superior electrocatalytic activities for oxygen reduction reaction. Abstract : Carbon nanomesh clusters have been prepared by a catalyst‐free, self‐sacrificial template strategy. The unique architecture with high specific surface area and hierarchically arranged pores exhibits excellent electrocapacitive performance and superior electrocatalytic activities for oxygen reduction reaction.